Efficacy of hand arm bimanual intensive therapy on upper limb co-ordination in a child with Rett syndrome: a case report - Chaitanya Prem; Nimmy Achankunju; Priyanka N. Somaiya (International Journal of Research in Medical Sciences, 2026)
Rett syndrome (RTT) is a severe, progressive, neurodevelopmental disorder, which affects predominantly females. RTT is characterized by developmental regression of spoken language and hand use that, with hand stereotypies and impaired ambulation, constitute the four core diagnostic features. Children with RTT exhibit significant impairments in purposeful hand use and bimanual coordination due to neurodevelopmental regression, yet structured bimanual intervention protocols are sparsely reported. The aim of the study is to find out the efficacy of hand arm bimanual intensive therapy on upper limb co-ordination in a child with RTT. This study involved a child of age 4 years diagnosed with RTT, selected based on predefined inclusion and exclusion criteria. Prior informed consent was obtained from the parent/caregiver of the subject. A pre-test assessment was conducted to evaluate upper limb coordination by bimanual fine motor function classification. The child underwent hand arm bimanual intensive therapy for 4 weeks, with session conducted of 35-40 minutes per day, 4 sessions per week. Following the intervention period, the post-test was assessed by same outcome measure as in pre-test. Following the four weeks of intervention, the participant showed progressive improvement in upper limb coordination and bimanual functional performance, with observable gains in voluntary use of hand. The magnitude of improvement ranged from mild to moderate as suggested in bimanual fine motor classification, suggesting positive effects of hand arm bimanual intensive therapy. Hand arm bimanual intensive therapy improved upper limb coordination in child with Rett syndrome following a 4-week intervention.